Multi-element solid waste-based high-strength thermal insulation concrete and preparation method thereof

By etching fly ash hollow microbeads and combining them with silica hydrophobic aerogel, the negative impact of fly ash hollow microbeads on the thermal conductivity of the aerogel and the poor compatibility with matrix gel materials are solved, and a multi-purpose solid waste-based insulation concrete with high strength and low thermal conductivity is achieved, and waste liquid is effectively utilized, reducing resource waste and environmental pollution.

CN119707416APending Publication Date: 2025-03-28HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890643.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing fly ash hollow microbeads have a negative impact on the thermal conductivity of the aerogel and have poor compatibility with the matrix gel material, resulting in a decrease in bond strength and the failure to effectively utilize the waste liquid, resulting in waste of resources and environmental pollution.

Method used

Porous hollow microbeads were prepared by etching the fly ash hollow microbeads using a mixed solution of NH4F and H3PO4, and combined with silica hydrophobic aerogel, and etching waste liquid and redispersible latex powder were added to prepare multi-purpose solid waste-based high-strength insulation concrete.

Benefits of technology

It reduces the thermal conductivity of concrete, improves its thermal insulation effect and compressive strength, and effectively utilizes etching waste liquid, reducing resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707416A_ABST
    Figure CN119707416A_ABST
Patent Text Reader

Abstract

The invention relates to multi-element solid waste-based high-strength thermal insulation concrete and a preparation method thereof, and belongs to the technical field of thermal insulation concrete. The problems that existing fly ash hollow microspheres have negative effects on the heat conductivity coefficient of aerogel and the compatibility of a composite material and a matrix gel material is poor are solved. The invention provides multi-element solid waste based high-strength thermal insulation concrete. The multi-element solid waste based high-strength thermal insulation concrete comprises the following components: granulated blast furnace slag, steel slag, silica fume, silicon dioxide hydrophobic aerogel-porous hollow microspheres, etching waste liquid and redispersible latex powder. The fly ash hollow microspheres are etched to obtain the porous hollow microspheres, so that solid-phase heat transfer is reduced, the overall thermal conductivity of the concrete is reduced, and the concrete has a good thermal insulation effect. The prepared silicon dioxide hydrophobic aerogel-porous hollow microspheres have good compatibility with a matrix and can be uniformly dispersed in the matrix. The waste liquid generated by etching is effectively utilized while the thermal insulation performance and compressive strength of the multi-element solid waste based high-strength thermal insulation concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal insulation concrete, and in particular relates to a multi-solid waste-based high-strength thermal insulation concrete and a preparation method thereof. Background Art

[0002] At present, inorganic thermal insulation materials commonly used in the construction field are mainly aerated concrete blocks, foamed concrete, cotton rock boards, thermal insulation mortar containing lightweight aggregates such as expanded perlite and vitrified microspheres, etc. These inorganic thermal insulation materials are widely used in exterior wall insulation and roof insulation of various buildings to meet the fire prevention and energy-saving requirements of different buildings. However, inorganic thermal insulation materials often have the problems of strong moisture absorption, poor crack resistance and low compressive strength.

[0003] Aerogel-hollow microsphere composite material combines the low thermal conductivity, low density and hydrophobicity of aerogel with the hard shell of fly ash hollow microspheres. It is a hydrophobic, low thermal conductivity and lightweight thermal insulation material. The use of aerogel-hollow microsphere composite material to prepare thermal insulation boards can reduce the water absorption rate of the thermal insulation boards while ensuring low thermal conductivity and high strength, thereby improving durability. However, there are the following problems in the preparation of aerogel-hollow microsphere composite materials: (1) Fly ash hollow microspheres have a great influence on the thermal conductivity of aerogel. After composite, the thermal conductivity of fly ash hollow microspheres is higher than that of aerogel, which has a negative impact on the low thermal conductivity of aerogel; (2) Since aerogel-hollow microsphere composite materials are hydrophobic, they have poor compatibility with matrix gel materials, are prone to uneven distribution and floating, resulting in reduced bonding strength; (3) The waste liquid after fly ash hollow microsphere treatment is not effectively utilized, resulting in resource waste and environmental pollution. Summary of the invention

[0004] In order to solve the negative impact of existing fly ash hollow microspheres on the thermal conductivity of aerogel and the poor compatibility of composite materials with matrix gel materials, the present invention provides a multi-solid waste-based high-strength thermal insulation concrete and a preparation method thereof.

[0005] The technical solution of the present invention:

[0006] A multi-solid waste-based high-strength thermal insulation concrete comprises the following components in parts by weight: 5.6-6.6 parts of granulated blast furnace slag, 2.8-3.3 parts of steel slag, 1.6-2.4 parts of silica fume, 1.4-2.1 parts of silica hydrophobic aerogel-porous hollow microspheres, 3.5 parts of etching waste liquid and 0.55 parts of redispersible latex powder; the particle size of the silica hydrophobic aerogel-porous hollow microspheres is 10-120 meshes.

[0007] Furthermore, the preparation method of the silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid comprises the following steps:

[0008] Step 1, pour fly ash hollow microbeads with a particle size of 10 to 120 meshes into water, screen the fly ash hollow microbeads floating on the upper layer of the water surface, and fully dry them for use; mix the H3PO4 solution and the NH4F solution, and stir at room temperature to obtain solution A; pour the dried fly ash hollow microbeads into the obtained solution A, and filter after ultrasonic dispersion to obtain modified fly ash hollow microbeads and etching waste liquid respectively; wash the obtained modified fly ash hollow microbeads until neutral, and fully dry them to obtain porous hollow microbeads;

[0009] Step 2: Mix water glass and deionized water, and pass through a strong acidic cation exchange resin after mechanical stirring to obtain a silica hydrosol; pour the porous hollow microbeads prepared in step 1 into the obtained silica hydrosol, collect the solid material after vacuum treatment, and perform a water bath to obtain a silica hydrogel-porous hollow microbeads;

[0010] Step 3, placing the silica hydrogel-porous hollow microspheres obtained in step 2 in anhydrous ethanol, filtering after water bath to obtain silica alcohol gel-porous hollow microspheres; placing the obtained silica alcohol gel-porous hollow microspheres in a trimethylchlorosilane / n-hexane mixed solution, filtering after water bath to obtain silica silylated gel-porous hollow microspheres; placing the obtained silica silylated gel-porous hollow microspheres in n-hexane solution, filtering to collect solid materials, standing for a certain period of time, and drying in a stepwise heating environment to obtain silica hydrophobic aerogel-porous hollow microspheres.

[0011] Furthermore, in step 1, the concentrations of the H3PO4 solution and the NH4F solution are both 1-2 mol / L, and the H3PO4 solution and the NH4F solution are mixed in equal volumes; the stirring speed is 300-360 r / min, and the stirring time is 30-40 min; the solid-liquid ratio of the fly ash hollow microspheres to solution A is 10-30 g:100 mL; the frequency of the ultrasonic dispersion is 60 kHz, and the time is 60-120 min; and the sufficient drying is drying at 80-110° C. for not less than 12 h.

[0012] Furthermore, in step 2, the modulus of the water glass is 3.3, and the volume ratio of the water glass to deionized water is 1:3-6; the rotation speed of the mechanical stirring is 300-360 r / min, and the stirring time is 30-40 min; the flow rate through the strong acid cation exchange resin is 200-300 mL / h; the pH of the silica hydrosol is 3-5; the solid-liquid ratio of the porous hollow microbeads to the silica hydrosol is 20-40 g:200 mL, the vacuum degree of the vacuum treatment is -0.03-0.08 MPa, the vacuum treatment time is 30 min, and the water bath is a constant temperature water bath at 40°C for 6 hours.

[0013] Furthermore, in step 3, the solid-liquid ratio of the silica hydrogel-porous hollow microspheres to anhydrous ethanol is 40-60 g:400 mL, and the solid-liquid ratio of the silica alcohol gel-porous hollow microspheres to trimethylchlorosilane / n-hexane mixed solution is 40-60 g:200 mL; the molar ratio of trimethylchlorosilane to n-hexane is 1:2-1:3, and the solid-liquid ratio of the silica silylated gel-porous hollow microspheres to n-hexane solution is 40-60 g:200 mL.

[0014] Furthermore, the water bath in step three is a constant temperature water bath at 40°C for 24 hours; the standing time is 24 hours, and the drying temperature of the drying treatment in the stepwise heating environment is 60°C, 80°C, 120°C and 160°C for 2 hours each.

[0015] Furthermore, the particle sizes of the granulated blast furnace slag and steel slag are both 400-600 meshes, and the granulated blast furnace slag and steel slag are both calcined at 600-800° C. for 12 hours; the particle size of the silica fume is 800-2500 meshes.

[0016] A method for preparing multi-solid waste-based high-strength thermal insulation concrete comprises mixing granulated blast furnace slag, steel slag, silica fume and silicon dioxide hydrophobic aerogel-porous hollow microspheres, adding etching waste liquid and redispersible latex powder and continuing to stir to obtain multi-solid waste-based high-strength thermal insulation concrete.

[0017] Furthermore, the rotation speeds of the mixed stirring and the continued stirring are both 140 r / min, the mixing stirring time is 6 min, and the continued stirring time is 5 min.

[0018] Furthermore, the obtained multi-solid waste-based high-strength thermal insulation concrete is loaded into a mold, compacted by vibration, and cured at a temperature of 60 to 80° C. for 12 hours. After demolding, standard curing is carried out at a temperature of 23 to 25° C. and a humidity of 99% for 28 days.

[0019] Beneficial effects of the present invention:

[0020] The present invention uses a mixed solution of NH4F and H3PO4 to etch fly ash hollow microspheres with a particle size of 10 to 120 meshes to obtain porous hollow microspheres, which reduces the solid phase heat transfer of the fly ash hollow microspheres, thereby reducing the thermal conductivity of the silica hydrophobic aerogel-porous hollow microspheres and the concrete as a whole, so that the concrete obtains a good thermal insulation effect. At the same time, the etched porous hollow microspheres, on the one hand, increase the activity of the volcanic ash, and on the other hand, the surface is rougher, thereby increasing the bonding force between the volcanic ash and the matrix; combined with the stimulating effect of the etching waste liquid on the granulated blast furnace slag, steel slag and silica ash multi-solid waste gelling materials and the auxiliary bonding effect of the redispersible latex powder, the density of the concrete is increased together, and the compressive strength of the concrete is improved.

[0021] The silica hydrophobic aerogel-porous hollow microspheres prepared by the invention have hydrophobicity and can be evenly dispersed in a matrix, so that the concrete has excellent fluidity and can be completely poured.

[0022] The present invention improves the thermal insulation performance and compressive strength of the multi-solid waste-based high-strength thermal insulation concrete and effectively utilizes the waste liquid generated by etching, thereby saving water resources and preventing the waste liquid from polluting the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 From left to right are the microscopic morphology images of the hydrophobic silica aerogel-porous hollow microbeads prepared in Example 1, which are enlarged step by step;

[0024] Figure 2 This is an energy spectrum analysis diagram of the silica hydrophobic aerogel-porous hollow microspheres prepared in Example 1;

[0025] Figure 3 This is a photo of the appearance of the multi-solid waste-based high-strength thermal insulation concrete test block prepared in Example 1;

[0026] Figure 4 This is a photo of the appearance of the concrete test block prepared in Comparative Example 1. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0028] Example 1

[0029] This embodiment provides a multi-solid waste-based high-strength thermal insulation concrete and a preparation method thereof.

[0030] The multi-solid waste-based high-strength thermal insulation concrete of this embodiment contains the following components in parts by weight:

[0031] 6.6 parts of granulated blast furnace slag, 3.3 parts of steel slag, 2.4 parts of silica fume, 2.1 parts of silica hydrophobic aerogel-porous hollow microspheres with a particle size of 10 to 20 meshes, 3.5 parts of etching waste liquid and 0.55 parts of redispersible latex powder.

[0032] The properties of the materials used to prepare the multi-solid waste-based high-strength thermal insulation concrete in this embodiment are described as follows:

[0033] (1) Granulated blast furnace slag:

[0034] The granulated blast furnace slag used in this embodiment has a particle size of 500-600 mesh and a bulk density of 2.8-3.0 g / m 3 , with a specific surface area of ​​220 to 500 m 2 / g, the main components are SiO2, Al2O3, and CaO, with contents of 28.9%, 17.96%, and 42.15% respectively. The high content of CaO in granulated blast furnace slag, stimulated by the etching waste liquid, helps to form calcium phosphate compounds, thus improving the early strength of the material; SiO2 and Al2O3 help to crosslink and further harden the network, thus enhancing the bonding of the overall structure.

[0035] The granulated blast furnace slag of this embodiment is activated by calcining at 800°C for 12 hours before use. The purpose of calcining is to destroy the glass phase of the granulated blast furnace slag. The granulated blast furnace slag contains a sparse amorphous glass phase, and this amorphous structure shows low reactivity in the early stage. Under high temperature conditions, the crystalline phase in the granulated blast furnace slag begins to stratify, promoting the dissolution of Ca, Si and Al, and increasing its reactivity with the activator.

[0036] (2) Steel slag:

[0037] The steel slag used in this embodiment has a particle size of 500-600 mesh and a bulk density of 1.5-2.5 g / cm 3 , specific surface area 320~500m 2 / g, and the main components are SiO2, Al2O3, CaO, Fe2O3, and MgO, with contents of 15.9%, 6.78%, 41.58%, 17.96%, and 8.15% respectively. The iron oxide and magnesium oxide contained in the steel slag form phosphate compounds (such as iron phosphate and magnesium phosphate) under the stimulation of phosphoric acid in the etching waste liquid, which enhances the long-term strength and durability of the material.

[0038] The steel slag of this embodiment is activated by calcining at 800°C for 12 hours before use. The purpose of calcining is to partially or remelt FeO and Fe2O3 in the steel slag at high temperature to produce highly active iron oxides. These iron oxides can react with the aluminosilicate structure under the action of an activator to form iron-based hydrates or other reaction products.

[0039] (3) Silica fume:

[0040] The silica fume used in this embodiment has a particle size of 2000-2500 mesh and a density of 650-800 kg / m 3 , specific surface area 24~30m 2 / g. SiO2 accounts for 87.6% of silica fume. The spherical morphology of silica fume can be filled between hydration products and particles, with a micro-nano filling effect; the silica fume is rich in active Si monomers and has high volcanic ash activity, which promotes polymerization reactions, allowing granulated blast furnace slag and steel slag matrix to generate more CSH and CASH gels, thereby improving mechanical properties.

[0041] (4) Redispersible latex powder:

[0042] The dispersible latex powder used in this embodiment is white powder, ethylene and vinyl acetate copolymer, and has a particle size of 80 to 120 μm. Its function is to form an emulsion after contacting water, and the polymer particles in the emulsion are deposited on the gelling material and the unhydrated solid waste and the silica hydrophobic aerogel-porous hollow microsphere particles, thereby increasing the bonding force between the gelling material, the solid waste and the silica hydrophobic aerogel-porous hollow microspheres, and reducing the porosity of the interface transition zone between the gelling material and the silica hydrophobic aerogel-porous hollow microspheres, making the interface transition zone structure more compact and improving the strength.

[0043] (5) Silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid:

[0044] The thermal conductivity of the silica hydrophobic aerogel-porous hollow microspheres prepared in this embodiment is 0.065-0.07 W / (m·k) and the bulk density is 0.2-0.25 g / cm 3 Its functions are: ① It acts as a thermal insulation filler to block heat transfer. ② The -CH3 group on the surface reduces the water absorption rate of the material and improves the durability of the thermal insulation concrete.

[0045] The etching waste liquid prepared in this embodiment contains HPO4 2- , HF, H2SiF6 and other substances. Its role is to dissolve the aluminosilicate structure (Al-O-Al, Si-O-Al) in steel slag and granulated blast furnace slag, and as aluminosilicate raw materials, the dissolved silicon and aluminum compounds repolymerize to form phosphates and polymer networks. Aluminum and phosphoric acid react to form aluminum phosphate gel, and silicon and phosphoric acid form a phosphate-containing polymer network. As the reaction proceeds, a geopolymer with a three-dimensional network structure is formed. This structure is connected by silicon oxygen (Si-O-Si), phosphorus oxygen (POP) and aluminum oxygen (Al-OP, Al-O-Si) bonds. - The Ca in slag and steel slag 2+ Mg 2+ CaF2 and MgF2 deposits are generated (Formula 1-5) with high compressive strength and chemical resistance.

[0046] CaO+H + +PO4 3- →Ca(H2PO4)2 (1)

[0047] SiO2+H + +PO4 3- →H2SiO3+HPO4 2- (2)

[0048] Al 3+ +HPO4 2- →Al(H2PO4)3 (3)

[0049] H2SiO3+HPO4 2- →(Si-OP) n +H2O (4)

[0050] Ca 2+ +Mg 2+ + F - →CaF2↓+ MgF2↓ (5)

[0051] This embodiment provides a method for preparing silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid, and the materials used for the preparation include:

[0052] 2.1 parts of 10-20 mesh fly ash hollow microspheres, 0.8 parts of water glass with a modulus of 3.3, 4 parts of strongly acidic cation exchange resin, 3 parts each of 1moL / LNH4F and 1moL / LH3PO4 solution, 4 parts of anhydrous ethanol, 4 parts of n-hexane, 0.8 parts of trimethylchlorosilane and 8 parts of deionized water.

[0053] The properties of the materials used to prepare the silica hydrophobic aerogel-porous hollow microspheres and the etching waste liquid are described as follows:

[0054] (1) Fly ash hollow microspheres:

[0055] The fly ash hollow microspheres used in this embodiment have a particle size of 10-20 mesh, a white shell forming a hollow structure, a wall thickness of 20-50 μm, and a bulk density of 0.21-0.23 g / cm 3 The thermal conductivity at room temperature is 0.081-0.1W / (m·k). The main components of fly ash hollow microspheres are SiO2, Al2O3, and CaO, with contents of 58.70%, 34.50%, and 1.22%, respectively. The main crystalline phases are mullite and quartz.

[0056] The functions of fly ash hollow microspheres are as follows: ① Using a solid shell to protect the low-strength aerogel and prevent the aerogel from breaking; ② The spherical structure optimizes the fluidity of the slurry, so that the thermal insulation filler is evenly distributed and stress concentration is reduced; ③ After etching, the surface perforation provides more active points, which helps the chemical groups on the surface to react with the calcium ions, silicate ions, etc. in the matrix to produce hydrated calcium silicate gel.

[0057] (2) Ammonium fluoride (NH4F):

[0058] The ammonium fluoride used in this example is a white crystalline powder with a density of 1.13 g / cm 3 , soluble in water, melting point is 98°C. Deliquescent, soluble in water, solubility in water at 0°C is 100g / 100mL.

[0059] (3) Phosphoric acid (H3PO4):

[0060] The phosphoric acid used in this embodiment is white crystals with a melting point of 42.35°C. Its functions are as follows: ① Mixing with NH4F to form HF to etch the fly ash hollow microspheres to prepare porous hollow microspheres (Formula 3), the bond energy of the Si-F bond is greater than the bond energy of the Si-O bond, and the fluorine ions can form a more stable Si-F bond with the Si ions in the glass phase on the surface of the fly ash hollow microspheres, forcing the Si-O bond in SiO2 to break, and forming perforations on the surface of the fly ash hollow microspheres for adsorbing the hydrosol. The reaction formulas are shown in (6) and (7).

[0061] H3PO4+NH4F→(NH4)H2PO4+HF (6)

[0062] HF+SiO2→H2SiF6+H2O (7)

[0063] (4) Water glass:

[0064] The water glass used in this embodiment is a transparent viscous liquid with a Na2O content of 8.3%, a SiO2 content of 26.5%, a modulus of 3.3 (industrial grade), and a Baume degree of 40.

[0065] (5) Strong acid cation exchange resin:

[0066] The particle size of the strong acid cation exchange resin used in this embodiment is 0.3-1.2 mm, and the exchange capacity is ≥1.8 Na. Its function is to remove the sodium ions in the water glass (Formula 8) to prevent the prepared aerogel from containing sodium chloride crystals that affect the thermal conductivity.

[0067] Na2SiO3+H + +H2O→Si(HO)4 (8)

[0068] (6) Anhydrous ethanol:

[0069] The absolute ethanol used in this example has a purity of 99.5%. Its function: the absolute ethanol can promote the chemical reaction of the silica hydrogel during the aging process, so that the siloxane bonds (Si-O-Si) are further cross-linked, and the network structure and mechanical stability of the gel are enhanced.

[0070] (7) n-Hexane:

[0071] The organic solvent used in this example is n-hexane, which has a molecular weight of 86.18 g / mol and a density of 0.655 g / cm 3 (20℃), surface tension is about 18.4mN / m. Its functions: ① As a solvent for surface hydrophobicizing agent, it combines with silanization agent TMCS to make the surface of silica aerogel hydrophobic, preventing aerogel from hygroscopicity and aging. ② Replace the water in the pores of aerogel. The low surface tension of n-hexane greatly reduces the capillary pressure, making the drying process more gentle.

[0072] (8) Trimethylchlorosilane (TMCS):

[0073] The trimethylchlorosilane used in this example is a silanization agent with a molecular weight of 108.64 g / mol and a density of 0.857 g / cm 3 (at 25°C). Its functions: ① The gel contains a large number of hydrophilic silanol groups (Si-OH). TMCS reacts with the silanol groups to generate trimethylsilyl groups (-Si(CH3)3) and hydrogen chloride, which changes the gel surface from hydrophilic to hydrophobic (Formula 9), making the aerogel-porous hollow microspheres moisture-resistant.

[0074] (CH3)3SiCl+Si-OH→Si-O-Si(CH3)3+HCl (9)

[0075] The specific preparation method of the hydrophobic silica aerogel-porous hollow microspheres and etching waste liquid in this embodiment includes the following preparation steps:

[0076] Step 1: Pour fly ash hollow microbeads with a particle size of 10-20 mesh into water, screen the fly ash hollow microbeads floating on the upper layer of the water surface, remove the fly ash hollow microbeads that sink to the bottom, and fully dry at 105°C.

[0077] The purpose of screening is to remove the broken fly ash hollow microbeads, which do not have a complete hollow structure and are unable to adsorb the hydrosol.

[0078] Mix 3 parts of 1 moL / L NH4F and 3 parts of 1 moL / L H3PO4 solution, stir at 360 r / min for 30 min at room temperature to obtain solution A; pour dry fly ash hollow microbeads into the obtained solution A at a solid-liquid ratio of 20 g:100 mL, ultrasonically disperse at a frequency of 60 kHz for 120 min and then filter to obtain modified fly ash hollow microbeads and etching waste liquid, respectively; wash the obtained modified fly ash hollow microbeads with deionized water until neutral, and dry at 110°C for not less than 12 h to obtain porous hollow microbeads.

[0079] The function of solution A is to remove the glass phase film on the surface of the hollow microspheres and form micron-sized perforations on the surface. The bond energy of the Si-F bond is greater than that of the Si-O bond. The fluoride ions can form more stable Si-F bonds with the Si ions in the glass phase on the surface of the fly ash hollow microspheres, forcing the Si-O bonds in SiO2 to break.

[0080] Step 2: Mix water glass with a modulus of 3.3 and deionized water in a volume ratio of 1:4, stir at 360 r / min for 30 min, and then pass through a strong acid cation exchange resin at a flow rate of 300 mL / h to remove sodium ions in the water glass to obtain a silica hydrosol with a pH of 3-4.

[0081] The silica hydrosol was absorbed into the cavity of the porous hollow microspheres by vacuum impregnation method: the silica hydrosol was placed in a vacuum barrel, and the porous hollow microspheres in step 1 were poured in a solid-liquid ratio of 20 g:100 mL, and the vacuum treatment was carried out at a vacuum degree of -0.08 MPa for 30 min, and the solid material was collected and placed in a constant temperature water bath at 40°C for 6 h to obtain silica hydrogel-porous hollow microspheres;

[0082] Step 3: placing the silica hydrogel-porous hollow microspheres obtained in step 2 in anhydrous ethanol at a solid-liquid ratio of 40 g:400 mL, keeping the mixture in a constant temperature water bath at 40° C. for 24 h, and filtering to obtain the silica hydrogel-porous hollow microspheres;

[0083] The obtained silica alcohol gel-porous hollow microspheres were placed in a trimethylsilyl chloride / n-hexane mixed solution at a solid-liquid ratio of 40 g:200 mL, wherein the molar ratio of trimethylsilyl chloride to n-hexane in the mixed solution was 1:2, and the mixture was placed in a constant temperature water bath at 40° C. for 24 h, and filtered to obtain silica silylated gel-porous hollow microspheres;

[0084] The obtained silica silylated gel-porous hollow microspheres were placed in n-hexane solution at a solid-liquid ratio of 40 g:200 mL, the solid material was collected by filtration, and after standing for 24 hours, it was dried at 60°C, 80°C, 120°C and 160°C for 2 hours each to obtain silica hydrophobic aerogel-porous hollow microspheres.

[0085] This embodiment provides a method for preparing multi-solid waste-based high-strength thermal insulation concrete, specifically:

[0086] Granulated blast furnace slag, steel slag, silica fume and silica hydrophobic aerogel-porous hollow microspheres were mixed and stirred at a stirring speed of 140 r / min for 6 minutes. After adding etching waste liquid and redispersible latex powder, stirring was continued at a stirring speed of 140 r / min for 5 minutes to obtain multi-solid waste-based high-strength thermal insulation concrete.

[0087] The multi-solid waste-based high-strength thermal insulation concrete of this embodiment is respectively loaded into 40×40×160mm and 40×40×40mm triple molds, compacted by vibration, and cured at 80°C for 12h. After demolding, it is cured for 28 days at a temperature of 23-25°C and a humidity of 99%.

[0088] The role of high-temperature curing is to promote the rearrangement of silicon-oxygen bonds (Si-O) and aluminum-oxygen bonds (Al-O) inside slag and steel slag, generate some new active phases (such as α-C2S, C3A, etc.), and make slag and steel slag easier to react with activators (acid phosphates) to generate strong products, such as CSH and NASH gels.

[0089] Example 2

[0090] This embodiment provides a multi-solid waste-based high-strength thermal insulation concrete and a preparation method thereof.

[0091] The multi-solid waste-based high-strength thermal insulation concrete of this embodiment contains the following components in parts by weight:

[0092] 6.6 parts of granulated blast furnace slag, 3.3 parts of steel slag, 2.4 parts of silica fume, 2.1 parts of silica hydrophobic aerogel-porous hollow microspheres with a particle size of 30 to 60 meshes, 3.5 parts of etching waste liquid and 0.55 parts of redispersible latex powder.

[0093] The materials used to prepare the silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid in this embodiment are as follows:

[0094] 2.1 parts of 30-60 mesh fly ash hollow microspheres, 0.8 parts of water glass with a modulus of 3.3, 4 parts of strongly acidic cation exchange resin, 3 parts each of 1moL / L NH4F and 1moL / L H3PO4 solution, 4 parts of anhydrous ethanol, 4 parts of n-hexane, 0.8 parts of trimethylchlorosilane and 8 parts of deionized water.

[0095] The preparation method of the hydrophobic silica aerogel-porous hollow microspheres and the etching waste liquid and the preparation method of the multi-solid waste-based high-strength thermal insulation concrete in this embodiment are the same as those in Example 1.

[0096] Example 3

[0097] This embodiment provides a multi-solid waste-based high-strength thermal insulation concrete and a preparation method thereof.

[0098] The multi-solid waste-based high-strength thermal insulation concrete of this embodiment contains the following components in parts by weight:

[0099] 6.6 parts of granulated blast furnace slag, 3.3 parts of steel slag, 2.4 parts of silica fume, 2.1 parts of silica hydrophobic aerogel-porous hollow microspheres with a particle size of 60-120 meshes, 3.5 parts of etching waste liquid and 0.55 parts of redispersible latex powder.

[0100] The materials used to prepare the silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid in this embodiment are as follows:

[0101] 2.1 parts of 60-120 mesh fly ash hollow microspheres, 0.8 parts of water glass with a modulus of 3.3, 4 parts of strongly acidic cation exchange resin, 3 parts each of 1moL / L NH4F and 1moL / L H3PO4 solution, 4 parts of anhydrous ethanol, 4 parts of n-hexane, 0.8 parts of trimethylchlorosilane and 8 parts of deionized water.

[0102] The preparation method of the hydrophobic silica aerogel-porous hollow microspheres and the etching waste liquid and the preparation method of the multi-solid waste-based high-strength thermal insulation concrete in this embodiment are the same as those in Example 1.

[0103] Comparative Example 1

[0104] This comparative example provides a concrete with aerogel-fly ash hollow microspheres as components and a preparation method thereof.

[0105] The concrete in this comparative example contains the following components by weight:

[0106] 6.6 parts of granulated blast furnace slag with a particle size of 500-600 mesh, 3.3 parts of steel slag with a particle size of 500-600 mesh, 2.4 parts of silica fume with a particle size of 2000-2500 mesh, 2.1 parts of aerogel-fly ash hollow microspheres with a particle size of 10-20 mesh and 3.5 parts of 1 moL / L phosphoric acid.

[0107] The materials used in this comparative example to prepare aerogel-fly ash hollow microspheres are as follows:

[0108] 2.1 parts of 10-20 mesh fly ash hollow microspheres, 0.8 parts of water glass with a modulus of 3.3, 4 parts of strongly acidic cation exchange resin and 8 parts of deionized water.

[0109] The preparation method of aerogel-fly ash hollow microspheres in this comparative example comprises the following steps:

[0110] Step 1: Pour the fly ash hollow microbeads into water, screen those floating on the water surface, remove the fly ash hollow microbeads that sink to the bottom, and fully dry them at 105°C.

[0111] Step 2: Mix water glass with a modulus of 3.3 and deionized water in a volume ratio of 1:4, stir at 360 r / min for 30 min, and pass through a strongly acidic cation exchange resin at a flow rate of 300 mL / h to obtain a silica hydrosol with a pH of 3-4.

[0112] Step 3: Put the silica hydrosol into a vacuum barrel, pour in the screened fly ash hollow microbeads at a solid-liquid ratio of 20g:100mL, vacuum treat for 30min at a vacuum degree of -0.08MPa, collect the solid material and place in a constant temperature water bath at 40°C for 6h to obtain hydrogel-fly ash hollow microbeads.

[0113] Step 4: Soak the hydrogel-fly ash hollow microspheres in anhydrous ethanol at a solid-liquid ratio of 40 g:400 mL, place in a constant temperature water bath at 40° C. for 24 h, and filter to obtain the alcohol gel-fly ash hollow microspheres.

[0114] Step 5: Pour the alcohol gel-fly ash hollow microspheres into a mixed solution of trimethylchlorosilane / n-hexane with a molar ratio of 1:2 at a solid-liquid ratio of 40 g:200 mL, place in a constant temperature water bath at 40° C. for 24 h, and filter to obtain silylated gel-fly ash hollow microspheres.

[0115] Step 6: Soak the silylated gel-fly ash hollow microspheres in n-hexane solution at a solid-liquid ratio of 40 g:200 mL, filter, let stand for 24 h, and dry at 60° C., 80° C., 120° C. and 160° C. for 2 h each to obtain aerogel-fly ash hollow microspheres.

[0116] The preparation method of concrete in this comparative example is specifically as follows:

[0117] Granulated blast furnace slag and steel slag were calcined at 800°C for 24 hours, mixed with silica fume and aerogel-fly ash hollow microspheres after calcination, stirred at a stirring speed of 140 r / min for 6 minutes, added with 1 mol / L phosphoric acid solution, and continued to stir at a stirring speed of 140 r / min for 5 minutes. The concrete was respectively filled into 40×40×160mm and 40×40×40mm triple molds, compacted by vibration, and cured at 80°C for 12 hours. After demolding, standard curing was carried out at a temperature of 23-25°C and a humidity of 99% for 28 days.

[0118] Comparative Example 2

[0119] This comparative example provides a concrete with polystyrene particles as components and a preparation method thereof.

[0120] The concrete in this comparative example contains the following components by weight:

[0121] 6.6 parts of granulated blast furnace slag with a particle size of 500-600 mesh, 3.3 parts of steel slag with a particle size of 500-600 mesh, 2.4 parts of silica fume with a particle size of 2000-2500 mesh, 4.2 parts of polystyrene particles with a particle size of 10-20 mesh, 3.5 parts of 1 moL / L phosphoric acid and 0.55 parts of redispersible latex powder.

[0122] The preparation method of the concrete of this comparative example comprises the following steps:

[0123] Step 1. Calcine the granulated blast furnace slag and steel slag at 800°C for 24 hours, mix them with silica fume and polystyrene particles after calcination, stir them at a stirring speed of 140r / min for 6 minutes, add 1moL / L phosphoric acid solution and 0.55 parts of redispersible latex powder, and continue to stir at a stirring speed of 140r / min for 5 minutes. Fill the concrete into 40×40×160mm and 40×40×40mm triple molds respectively, vibrate and compact, and cure at 80°C for 12 hours. After demolding, standard curing is carried out for 28 days at a temperature of 23-25°C and a humidity of 99%.

[0124] Figure 1 From left to right are the microscopic morphology images of the hydrophobic silica aerogel-porous hollow microbeads prepared in Example 1, which are enlarged step by step; Figure 1 It can be seen that the fly ash hollow microspheres are etched with a mixed solution of NH4F and H3PO4, and the shell of the fly ash hollow microspheres becomes thinner, forming micron-level pores on the surface. The perforation provides more active points, which helps the chemical groups on the surface of the microspheres to produce stronger chemical reactions with calcium ions, silicate ions, etc. in the matrix. Moreover, the surface of the fly ash hollow microspheres is rough after etching, and mechanical interlocking can be formed when in contact with the matrix, thereby increasing the interfacial friction and bonding force between it and the matrix. Further magnification shows that after vacuum impregnation, the silica hydrosol is absorbed into the cavity of the porous hollow microspheres.

[0125] Figure 2 : is the energy spectrum analysis diagram of the silica hydrophobic aerogel-porous hollow microspheres prepared in Example 1; Table 1 is the obtained energy spectrum analysis data;

[0126] Table 1

[0127]

[0128]

[0129] It can be seen from the energy spectrum analysis diagram and analysis data that the main O (31.34%) and Si (38.27%) in the cavity are the main components of silica aerogel, and C (12.61%) is modified by trimethylchlorosilane ((CH3)3SiCl) on silica aerogel-porous hollow microspheres, and the hydrophobic -CH3 group replaces the hydrophilic -OH group. The above element proportions prove that the substance absorbed into the cavity of the porous hollow microspheres is silica aerogel.

[0130] The performances of the silica hydrophobic aerogel-porous hollow microspheres, aerogel-fly ash hollow microspheres and polystyrene particles in Examples 1 to 3 and Comparative Examples 1 and 2 are compared, and the results are shown in Table 2.

[0131] Table 2

[0132]

[0133] As can be seen from the data in Table 2, the thermal conductivity of the silica hydrophobic aerogel-porous hollow microspheres prepared by the present invention is significantly lower than that of the aerogel-fly ash hollow microspheres, and the thermal conductivity of the 10-20 mesh silica hydrophobic aerogel-porous hollow microspheres is lower than that of the 30-60 mesh and 60-120 mesh silica hydrophobic aerogel-porous hollow microspheres. This is because the hollow structure of the silica hydrophobic aerogel-porous hollow microspheres makes the flow rate and density of the gas small, the Reynolds number is small, and it is difficult for the gas in the ball to turbulently form turbulence, and the heat transfer rate of the gas molecules is slow, and there is a lower thermal conductivity. After being treated with a mixed solution of NH4F and H3PO4, the shell of the fly ash hollow microspheres becomes thinner, reducing the solid phase heat transfer of the fly ash hollow microspheres; micron-level pores are formed on the surface, further reducing solid heat transfer, weakening heat flow transfer, reducing the thermal conductivity of the fly ash hollow microspheres, and making the composite material have a lower thermal conductivity.

[0134] The crushing strength of the silica hydrophobic aerogel-porous hollow microspheres prepared by the present invention is more than 10 times that of polystyrene particles. This is because the fly ash hollow microspheres have a hard shell and have higher strength after being combined with the aerogel.

[0135] Figure 3 This is a photo of the appearance of the multi-solid waste-based high-strength thermal insulation concrete test block prepared in Example 1; Figure 4 This is a photo of the appearance of the concrete test block prepared in Comparative Example 1. Figure 3 and Figure 4 From the comparison of the pictures, it can be seen that the fly ash hollow microspheres in comparative document 1 have poor adhesion to the matrix, resulting in the floating of the fly ash hollow microspheres. The present invention uses redispersible latex powder to increase the adhesion between the cementitious material and the silica hydrophobic aerogel-porous hollow microspheres to prevent them from floating during vibration. The multi-solid waste-based high-strength thermal insulation concrete prepared by the present invention can be cast completely, and the silica hydrophobic aerogel-porous hollow microspheres in the obtained test blocks have high bonding strength with the matrix, and can be dispersed more evenly. The porosity of the interface transition zone between the silica hydrophobic aerogel-porous hollow microspheres and the matrix is ​​smaller, making the interface transition zone structure denser and having higher flexural strength.

[0136] The compressive strength, thermal conductivity and other tests were performed on the concrete of Examples 1 to 3 and Comparative Examples 1 and 2 after curing. The test results are shown in Table 3.

[0137] Table 3

[0138]

[0139] From the data in Table 3, it can be seen that the concrete test block containing silica hydrophobic aerogel-porous hollow microspheres with a particle size of 10-20 meshes in Example 1 has lower thermal conductivity, higher compressive strength and flexural strength, lower water absorption, and better comprehensive performance. However, the fly ash hollow microspheres in Comparative 1 have poor adhesion to the matrix and no valid data can be obtained.

[0140] The spherical structure of the silica hydrophobic aerogel-porous hollow microspheres in the present invention plays a roller role, optimizes the fluidity of the slurry, makes the silica hydrophobic aerogel-porous hollow microspheres more evenly distributed in the matrix, reduces the stress concentration when subjected to force, forms more thermal insulation areas inside the matrix, extends the heat transfer path, and the heat conduction inside the material is diffused multiple times, thereby reducing the overall thermal conductivity.

[0141] The present invention can remove the glass phase film on the surface of fly ash hollow microspheres and form perforations through the mixed solution of NH4F and H3PO4, which can improve the activity of volcanic ash, so that the active SiO2 in the hollow microspheres reacts with the Ca(OH)2 produced by hydration to generate CSH, which is interwoven in the gap between the hollow microspheres and the cementitious material. On the other hand, the surface of the fly ash hollow microspheres is made rough, and mechanical interlocking can be formed when in contact with the matrix, which significantly improves the interface friction and bonding force between the matrix and the matrix. 2- Etching waste liquids containing HF, H2SiF6 and other materials can dissolve the aluminum silicate structure (Al-O-Al, Si-O-Al) in steel slag and granulated blast furnace slag, and the dissolved silicon and aluminum compounds repolymerize to form phosphates and polymer networks. Aluminum and phosphoric acid react to form aluminum phosphate gel, and silicon and phosphoric acid form a phosphate-containing polymer network. This structure is connected by silicon oxygen (Si-O-Si), phosphorus oxygen (POP) and aluminum oxygen (Al-OP, Al-O-Si) bonds, and has high compressive strength and chemical resistance. [PO4] in etching waste liquid 3- The tetrahedrons bond with the active Al in slag and steel slag to form a three-dimensional Si-O-Al-OP network structure. 2- Continue to react with the hydration product Ca(OH)2 to generate CSH, F - With Ca 2+ Mg 2+ CaF2 and MgF2 deposits are generated to fill the open pores left in the cement matrix due to water evaporation, making the matrix more compact. High temperature curing promotes the chemical reaction between phosphoric acid and the active components in steel slag or slag (such as calcium oxide, aluminum oxide, etc.), accelerates the formation of calcium phosphate, aluminum phosphate and other products inside the coagulation material, increases the density of the material, and improves the compressive strength.

[0142] The invention uses trimethylchlorosilane modification to make the aerogel-porous hollow microsphere material hydrophobic, so that even if a porous structure is formed inside the concrete, the concrete still has a low water absorption rate.

Claims

1. A multi-solid waste-based high-strength thermal insulation concrete, characterized in that: The invention comprises the following components in parts by weight: 5.6 to 6.6 parts of granulated blast furnace slag, 2.8 to 3.3 parts of steel slag, 1.6 to 2.4 parts of silica fume, 1.4 to 2.1 parts of silica hydrophobic aerogel-porous hollow microspheres, 3.5 parts of etching waste liquid and 0.55 parts of redispersible latex powder; the particle size of the silica hydrophobic aerogel-porous hollow microspheres is 10 to 120 meshes.

2. The multi-solid waste-based high-strength thermal insulation concrete according to claim 1, characterized in that: The method for preparing the silica hydrophobic aerogel-porous hollow microspheres and etching waste liquid comprises the following steps: Step 1, pour fly ash hollow microbeads with a particle size of 10 to 120 meshes into water, screen the fly ash hollow microbeads floating on the upper layer of the water surface, and fully dry them for use; mix the H3PO4 solution and the NH4F solution, and stir at room temperature to obtain solution A; pour the dried fly ash hollow microbeads into the obtained solution A, and filter after ultrasonic dispersion to obtain modified fly ash hollow microbeads and etching waste liquid respectively; wash the obtained modified fly ash hollow microbeads until neutral, and fully dry them to obtain porous hollow microbeads; Step 2: Mix water glass and deionized water, and pass through a strong acidic cation exchange resin after mechanical stirring to obtain a silica hydrosol; pour the porous hollow microbeads prepared in step 1 into the obtained silica hydrosol, collect the solid material after vacuum treatment, and perform a water bath to obtain a silica hydrogel-porous hollow microbeads; Step 3, placing the silica hydrogel-porous hollow microspheres obtained in step 2 in anhydrous ethanol, filtering after water bath to obtain silica alcohol gel-porous hollow microspheres; placing the obtained silica alcohol gel-porous hollow microspheres in a trimethylchlorosilane / n-hexane mixed solution, filtering after water bath to obtain silica silylated gel-porous hollow microspheres; placing the obtained silica silylated gel-porous hollow microspheres in n-hexane solution, filtering to collect solid materials, standing for a certain period of time, and drying in a stepwise heating environment to obtain silica hydrophobic aerogel-porous hollow microspheres.

3. The multi-solid waste-based high-strength thermal insulation concrete according to claim 2, characterized in that: Step 1: The concentrations of the H3PO4 solution and the NH4F solution are both 1-2 mol / L, and the H3PO4 solution and the NH4F solution are mixed in equal volumes; the stirring speed is 300-360 r / min, and the stirring time is 30-40 min; the solid-liquid ratio of the fly ash hollow microspheres to solution A is 10-30 g:100 mL; the frequency of the ultrasonic dispersion is 60 kHz, and the time is 60-120 min; the sufficient drying is dried at 80-110° C. for not less than 12 h.

4. The multi-solid waste-based high-strength thermal insulation concrete according to claim 3, characterized in that: Step 2: The modulus of the water glass is 3.3, and the volume ratio of the water glass to deionized water is 1:3-6; the rotation speed of the mechanical stirring is 300-360 r / min, and the stirring time is 30-40 min; the flow rate through the strong acid cation exchange resin is 200-300 mL / h; the pH of the silica hydrosol is 3-5; the solid-liquid ratio of the porous hollow microspheres to the silica hydrosol is 20-40 g:200 mL, the vacuum degree of the vacuum treatment is -0.03-0.08 MPa, the vacuum treatment time is 30 min, and the water bath is a constant temperature water bath at 40°C for 6 hours.

5. The multi-solid waste-based high-strength thermal insulation concrete according to claim 4, characterized in that: In step 3, the solid-liquid ratio of the silica hydrogel-porous hollow microspheres to anhydrous ethanol is 40-60 g:400 mL, and the solid-liquid ratio of the silica alcohol gel-porous hollow microspheres to trimethylchlorosilane / n-hexane mixed solution is 40-60 g:200 mL; the molar ratio of trimethylchlorosilane to n-hexane is 1:2-1:3, and the solid-liquid ratio of the silica silylated gel-porous hollow microspheres to n-hexane solution is 40-60 g:200 mL.

6. The multi-solid waste-based high-strength thermal insulation concrete according to claim 5, characterized in that: The water bath in step 3 is kept at a constant temperature of 40°C for 24 hours; the standing is for 24 hours, and the drying temperature of the drying treatment in the stepwise heating environment is 60°C, 80°C, 120°C and 160°C for 2 hours each.

7. A multi-solid waste-based high-strength thermal insulation concrete according to any one of claims 1 to 6, characterized in that: The particle sizes of the granulated blast furnace slag and steel slag are both 400-600 meshes, and the granulated blast furnace slag and steel slag are both calcined at 600-800° C. for 12 hours; the particle size of the silica fume is 800-2500 meshes.

8. A method for preparing multi-solid waste-based high-strength thermal insulation concrete as claimed in any one of claims 1 to 7, characterized in that: Granulated blast furnace slag, steel slag, silica fume and silica hydrophobic aerogel-porous hollow microspheres are mixed and stirred, and etching waste liquid and redispersible latex powder are added and continued to be stirred to obtain multi-solid waste-based high-strength thermal insulation concrete.

9. The method for preparing multi-solid waste-based high-strength thermal insulation concrete according to claim 8, characterized in that: The rotation speeds of the mixing and stirring and the continued stirring were both 140 r / min, the mixing and stirring time was 6 min, and the continued stirring time was 5 min.

10. The method for preparing multi-solid waste-based high-strength thermal insulation concrete according to claim 9, characterized in that: The obtained multi-solid waste-based high-strength thermal insulation concrete is loaded into a mold, compacted by vibration, and cured at a temperature of 60-80°C for 12 hours. After demolding, standard curing is carried out at a temperature of 23-25°C and a humidity of 99% for 28 days.